Dual anti-CTLA-4 and anti-PD-1 blockade in metastatic basal cell carcinoma - Patel, Sandip P.; Cano-Linson, Eleanor; Chae, Young Kwang; Schokrpur, Shiruyeh; Lao, Christopher D.; Powers, Benjamin C.; Victor, Adrienne I.; Onitilo, Adedayo A.; Shin, Sarah; Takebe, Naoko; Threlkel, Sara; McLeod, Christine M.; et al. (NPJ precision oncology, 2025)
We report the basal cell cancer (BCC) cohort of the SWOG/NCI 1609 Dual Anti-CTLA-4 & Anti-PD-1 blockade in Rare Tumors (DART), a phase II prospective, multicenter basket trial of nivolumab and ipilimumab. The primary endpoint was objective response rate (ORR) (RECIST v1.1). Overall survival (OS), progression-free survival (PFS), and toxicity were secondary endpoints. Sixteen patients with advanced/metastatic BCC were evaluable. The ORR was 31% (95% CI, 19–50%), and the 12-month OS, 75% (95% CI, 57–100%). Median PFS was 9.3 months (95% CI, 3.3–NA). Of 15 patients evaluable for clinical benefit, five partial responses (PRs) and five stable disease >6 months (total = 10/15 (66.7%)) were seen. The most common toxicities included fatigue (37.5%), pruritis (31.3%), and diarrhea (25%). In patients with advanced/metastatic BCC, ipilimumab and nivolumab produced an ORR of 31% and prolonged (>6 months) PFS in 73% of patients, with seven PFS/iPFS of >1 year, including one with prior anti-PD-1. ClinicalTrials.gov ID: NCT02834013 (Registered 7/15/2016; https://clinicaltrials.gov/ct2/show/NCT02834013 ).